Prevalence of attention-deficit/hyperactivity disorder in individuals with autism spectrum disorder: A meta-analysis - Rong, Ying; Yang, Chang-Jiang; Jin, Ye; Wang, Yue (Research in autism spectrum disorders, 2021)
•This research provides a meta-analysis of studies on the prevalence of ADHD in ASD.•The pooled estimate of the current prevalence of ADHD in ASD was 38.5 %.•The pooled estimate of the lifetime prevalence of ADHD in ASD was 40.2 %.•Age, IQ, recruitment setting, and diagnostic criteria influenced the current prevalence. Comorbidity with attention-deficit/hyperactivity disorder (ADHD) is very common in autism spectrum disorder (ASD), worsening the developmental trajectory of ASD. The reported rates of ADHD in ASD vary widely. However, no meta-analysis has been conducted specifically to assess both the current and lifetime prevalence of ADHD in ASD. This study aims to fill in this gap. We searched the Web of Science, PubMed, PsycINFO, CINAHL, and Embase databases for eligible articles published between January 1, 2000, and September 5, 2020. The risk of bias tool was used to assess the studies’ quality. Overall pooled estimates of the current and lifetime prevalence of ADHD in ASD were obtained using random-effects models. Study heterogeneity was examined by Q and I2 statistics. A total of 63 articles were eventually included, of which 56 studies reported the current prevalence, and 13 studies reported the lifetime prevalence. The results revealed that the pooled current and lifetime prevalence rates of ADHD among ASD were 38.5 % (95 % CI 34.0–43.2) and 40.2 % (95 % CI 34.9–45.7), respectively. Our study also confirmed that age, intellectual disability, recruitment settings, and diagnostic criteria significantly influenced the current prevalence of ADHD in ASD. ASD has considerable high current or lifetime prevalence rates of co-occurring ADHD. The findings demonstrate that clinicians should consider the high prevalence of ADHD in ASD and especially stay alert to possible ADHD diagnoses in school-age children and adolescents with ASD. Medical institutions should improve the assessment and tracking system of ADHD comorbidity in ASD and maximize the diagnostic accuracy for better treatment.